Shaping Oncogenic Microenvironments: Contribution of Fibronectin - Gemma Guerrero-Barberà; Natalia Burday; Mercedes Costell (Frontiers in Cell and Developmental Biology, 2024)
The extracellular matrix (ECM) is a complex network of proteins and glycans, dynamically remodeled and specifically tailored to the structure/function of each organ. The malignant transformation of cancer cells is determined by both cell intrinsic properties, such as mutations, and extrinsic variables, such as the mixture of surrounding cells in the tumor microenvironment and the biophysics of the ECM. During cancer progression, the ECM undergoes extensive remodeling, characterized by disruption of the basal lamina, vascular endothelial cell invasion, and development of fibrosis in and around the tumor cells resulting in increased tissue stiffness. This enhanced rigidity leads to aberrant mechanotransduction and further malignant transformation potentiating the de-differentiation, proliferation and invasion of tumor cells. Interestingly, this fibrotic microenvironment is primarily secreted and assembled by non-cancerous cells. Among them, the cancer-associated fibroblasts (CAFs) play a central role. CAFs massively produce fibronectin together with type I collagen. This review delves into the primary interactions and signaling pathways through which fibronectin can support tumorigenesis and metastasis, aiming to provide critical molecular insights for better therapy response prediction.